The Influence of Activity-Based Workplace, Work-Life Balance, and Employee Engagement on Performance - Alghamsah, Moch. Hasbi; Rahayu, Sri; Fitrianty, Rifda; Sundjoto, Sundjoto (LifeSciFi, 2025)
Employee performance is critical to the success of an organization, especially the public sector. This study aims to analyze the influence of Activity Based Workplace, Work Life Balance, and Employee Engagement on Employee Performance at Madya Dua Tax Office West Jakarta. A quantitative approach was used with multiple linear regression analysis as the method. The sample consisted of 58 employees, determined using the Slovin formula from the population of active employees at tax office. Data were collected through the distribution of questionnaires and analyzed using SPSS 25.0. The results show that simultaneously, the three independent variables, Activity Based Workplace, Work Life Balance, and Employee Engagement have a significant effect on employee performance. Partially, each of these variables also shows a significant influence with a positive regression coefficient. This indicates that the better the implementation of an activity-based work environment, the balance between work and personal life, and employee engagement, the higher the employee performance. These findings imply that Madya Dua Tax Office West Jakarta should continuously improve the quality of the work environment, support work-life balance, and strengthen employee engagement to achieve optimal organizational performance.